Living fast and dangerously? Spatio‐temporalities of happy and healthful smoking futures. Issue 1 (31st July 2015) - Tan, Qian Hui
Abstract : This paper gathers together young smokers' senses of present‐futures in the context of Singapore, where smoking is generally frowned upon. Accordingly, I examine how young smokers perceive and perform a multiplicity of healthful subjectivities, which is set within the context of an aggressive state‐driven pre‐emptive politics striving to nip the 'problem' of smoking in the bud. In providing a range of justifications for their smoking practices, young smokers have attempted to redefine their own spaces of healthfulness and happiness beyond those imposed by public health discourses. More specifically, although some of them are able to recognize the mutual imbrication of the present and future, others are more inclined to privilege the here‐and‐now over the there‐and‐then. In this way I disrupt stereotypes of young people as being only emblems of the future and as passive victims of their own irresponsibility. Rather, I argue that in responding creatively to anti‐smoking messages that propagate the inevitability of dystopic smoking destinies, young smokers play an active role in reproducing their own futural geographies. In so doing, I hope to extend critical geographical perspectives by highlighting the influence that the future can have on the spatio‐temporalities that young people experience.